Environmental drivers of ranging behavior in the Javan gibbon (Hylobates moloch) - ALINA SIMOKAR; ELHAM SUMARGA; RAHAYU OKTAVIANI; YOGI PRASETIO (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Simokar A, Sumarga E, Oktaviani R, Prasetio Y. 2025. Environmental drivers of ranging behavior in the Javan gibbon (Hylobates moloch). Biodiversitas 26: 3903-3915. Environmental factors and food availability shape the foraging strategies and ranging behavior of primates. The Javan gibbon (Hylobates moloch), endemic to Java Island, Indonesia, inhabits the remaining forest patches such as Gunung Halimun Salak National Park (GHSNP). This study investigated the effects of environmental variables and food availability on Javan gibbon ranging in GHSNP, using behavioral and ecological data collected from January to December 2022. We observed three habituated gibbon groups through scan sampling and collected monthly plant phenology and daily temperature and rainfall data. The data were analyzed to: (i) calculate the activity budget; (ii) map and quantify ranging patterns, using QGIS; (iii) determine the Food Abundance Index (FAI); (vi) calculate mean monthly temperature and rainfall; (v) analyze the effects of environmental conditions and food availability on ranging behaviour/pattern using linear mixed models in RStudio. Results showed that Javan gibbon activities were dominated by resting, followed by feeding, locomotion, and social interaction. The mean home range size and daily path length were 38.68±7.17 ha and 3.25±0.30 km, respectively. Important food sources included Ficus spp., Cordia bantamensis, Sandoricum koetjape, and Knema cinerea with the highest FAI values for fruits, young leaves, and flowers occurred in September, July, and March, respectively. The average minimum temperature, maximum temperature, and monthly rainfall were 17.77±0.34?, 26.59±0.76?, and 418.23±179.68 mm, respectively. Ranging patterns were significantly affected by rainfall, temperature, and food availability (p-value<0.05), with observed differences among groups due to food resources distribution, foraging strategies, and environmental responses.